An experimental investigation of heat transfer characteristics of water based Al2O3 nanofluid operated shell and tube heat exchanger with air bubble injection technique - Thakur, Gaurav; Singh, Gurpreet (International Journal of Engineering and Technology, 2017)
The thermal performance of shell and tube heat exchangers has been enhanced with the use of different techniques. Air bubble injection is one such promising and inexpensive technique that enhances the heat transfer characteristics inside shell and tube heat exchanger by creating turbulence in the flowing fluid. In this paper, experimental study on heat transfer characteristics of shell and tube heat exchanger was done with the injection of air bubbles at the tube inlet and throughout the tube with water based Al2O3 nanofluids i.e. (0.1%v/v and 0.2%v/v). The outcomes obtained for both the concentrations at two distinct injection points were compared with the case when air bubbles were not injected. The outcomes revealed that the heat transfer characteristics enhanced with nanoparticles volumetric concentration and the air bubble injection. The case where air bubbles were injected throughout the tube gave maximum enhancement followed by the cases of injection of air bubbles at the tube inlet and no air bubble injection. Besides this, water based Al2O3 nanofluid with 0.2%v/v of Al2O3 nanoparticles gave more enhancement than Al2O3nanofluid with 0.1%v/v of Al2O3 nanoparticles as the enhancement in the heat transfer characteristics is directly proportional to the volumetric concentration of nanoparticles in the base fluid. The heat transfer rate showed an enhancement of about 25-40% and dimensionless exergy loss showed an enhancement of about 33-43% when air bubbles were injected throughout the tube. Moreover, increment in the heat transfer characteristics was also found due to increase in the temperature of the hot fluid keeping the flow rate of both the heat transfer fluids constant.
Keywords: Shell and Tube Heat Exchanger; Al2O3/Water Based Nanofluids; Heat Transfer Coefficient; Overall Heat Transfer Coefficient; Nusselt Number.